Thickness of the aqueous boundary layer in stirred microtitre plate permeability assays (PAMPA and Caco-2), based on the Levich equation - Alex Avdeef (International Association of Physical Chemists (IAPC), 2022)
The stirring frequency exponent of -1/2 in the theoretical Levich expression appears to apply to PAMPA and Caco-2 assays, where efficient individual-well magnetic stirring ( > 20 RPM) is used.  If a single molecule is used as a stirring calibrant, then scaling suggested by Eq. (5) with microtitre plate data may be used.  The error in calculating hABL based on unscaled hABLref can be as high as 30%.  This is of practical importance in PAMPA, and perhaps cellular assays as well.